2022
DOI: 10.1136/rapm-2022-103550
|View full text |Cite
|
Sign up to set email alerts
|

Association of anesthesia and analgesia with long-term mortality after hip fracture surgery: an analysis of the Australian and New Zealand hip fracture registry

Abstract: IntroductionHip fractures are a common frailty injury affecting a vulnerable geriatric population. It is debated if anesthetic and analgesic techniques are associated with altered risk for outcomes in hip fracture patients. This study aimed to determine the association of anesthesia and regional analgesia with all cause 12-month mortality and even longer-term mortality after hip fracture surgery in Australia and New Zealand.MethodsData from the Australian and New Zealand Hip Fracture Registry collected from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…They found that "overall rates of mortality were significantly lower in the spinal anesthesia cohort compared to the general anesthesia cohort." This same mortality advantage for spinal anesthesia was not seen by investigators utilizing the Australian and New Zealand Hip Fracture Registry 5 . Evaluating 17,635 patients who underwent hip fracture surgery, the authors reported finding no difference in 12-month mortality for the 2 types of anesthesia (general and spinal) (p = 0.238).…”
Section: Hip Fracture Managementsupporting
confidence: 58%
See 1 more Smart Citation
“…They found that "overall rates of mortality were significantly lower in the spinal anesthesia cohort compared to the general anesthesia cohort." This same mortality advantage for spinal anesthesia was not seen by investigators utilizing the Australian and New Zealand Hip Fracture Registry 5 . Evaluating 17,635 patients who underwent hip fracture surgery, the authors reported finding no difference in 12-month mortality for the 2 types of anesthesia (general and spinal) (p = 0.238).…”
Section: Hip Fracture Managementsupporting
confidence: 58%
“…The authors reported that 3,768 patients who received a spinal anesthetic had a longer length of stay compared with patients who received general anesthesia but lower rates of systemic sepsis, cardiac arrest, and blood transfusion. They found that “overall rates of mortality were significantly lower in the spinal anesthesia cohort compared to the general anesthesia cohort.” This same mortality advantage for spinal anesthesia was not seen by investigators utilizing the Australian and New Zealand Hip Fracture Registry 5 . Evaluating 17,635 patients who underwent hip fracture surgery, the authors reported finding no difference in 12-month mortality for the 2 types of anesthesia (general and spinal) (p = 0.238).…”
Section: Hip Fracture Managementsupporting
confidence: 58%
“…Regional anesthesia use has expanded into nearly every surgical specialty and most anesthesia clinical practices, with demonstrated benefits in better acute pain control, fewer perioperative complications, improved recovery outcomes, less resource utilization, 1,2 and improved long-term mortality 3 . Despite the current momentum on early recovery after surgery and emphasis on opioid-reducing anesthesia and analgesia, the percentage of patients receiving perioperative nerve blocks has significant geographic and surgical procedure-specific variations and remains low, ranging from 12.5% in the United States for total joint arthroplasty to about 40% in hip fractures in Australia and New Zealand 3,4 . The most important factor for eligible patients not receiving nerve blocks is at the anesthesia provider level 5 .…”
mentioning
confidence: 99%
“…3 Despite the current momentum on early recovery after surgery and emphasis on opioid-reducing anesthesia and analgesia, the percentage of patients receiving perioperative nerve blocks has significant geographic and surgical procedure-specific variations and remains low, ranging from 12.5% in the United States for total joint arthroplasty to about 40% in hip fractures in Australia and New Zealand. 3,4 The most important factor for eligible patients not receiving nerve blocks is at the anesthesia provider level. 5 Thus, there is a growing need for proficiency training for both trainees and practicing anesthesiologists in high-value peripheral nerve blocks, similar to what we have achieved with spinal and epidural anesthesia.The purpose of this review article is to summarize the current state of regional anesthesia education and training per Accreditation Council for Graduate Medical Education (ACGME) regulation, provide an overview of the common training modalities and assessment tools employed in residency and regional anesthesia and acute pain medicine (RAAPM) fellowship programs in North American, obstacles encountered by training institutions and challenges faced by educators and trainees, as well as implications for future directions.…”
mentioning
confidence: 99%
See 1 more Smart Citation